The impact of an Oral Health Education (OHE) program by teachers and mothers on adolescents' oral health - Sally T Daaj; Zainab A Al Dahan (College of Dentistry/ University of Baghdad, 2018)
Background: Adolescence is one of the most dynamic stages of human development. However, Oral health is an integral part of public health, significantly impacts on the quality of life. OHE program is an important issue that should be given to them. The aim of this study was to evaluate oral health outcomes on adolescents' oral health by teachers and mothers Materials and Methods: The study was carried out in seven schools of Diyala - Baquba city. This 14-weeks duration study assessed the effectiveness of school OHE program on oral hygiene status, gingival health, and halitosis assessment of 80, 12 year-old, both genders of school adolescents. From the selected schools, one group was supervised by the teachers and the other was supervised by the mothers. General and oral health assessments were evaluated using a questionnaire. A three days training workshop was organized for the teachers and mothers. Oral hygiene, gingival health, and halitosis assessment were assessed using plaque indices, gingival indices and halitosis scores respectively. the resulting data were statistically analyzed using SPSS version 20. Results: Plaque, gingival and halitosis scores reductions were highly significant. Results recorded gingival index, and halitosis scores were lower among the teacher-led group compared to the mother-led group. Statistically, high significant differences were found (P< 0.01).But there is no significant differences were noticed between the groups for plaque index (p>0.05). Conclusions: The OHE program was effective in teacher-led group than mother-led group in improving oral hygiene status, gingival health and halitosis scores of adolescents.